(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Polycystic ovary syndrome is the most common ovary disorder characterize by complex of health problems that affects women of reproductive age due to hormonal imbalance and metabolic problems, so nurses have an important role in providing counseling and health education for women in reproductive age. Objectives: To assess nurses knowledge about Polycystic ovary syndrome. Methodology: A descriptive study was conducted on probability sample (systematic random) of (100) nurses and midwife who work in obstetric and gynecological departments from three hospitals at Baghdad City: AL-Karkh maternity Hospital, Al-Elwia Maternity Teaching Hospital and Baghdad Teaching Hospital. Study implemented for the period of February 24th 2015 to April 25th 2015. A questionnaire was used as a tool of data collection to fulfill with objective of the study and consisted of three parts, including demographic characteristics, personal experience with polycystic ovary syndrome, sources of knowledge regarding polycystic ovary syndrome and knowledge regarding polycystic ovary syndrome. A pilot study was carried out to test the reliability of the questionnaire and content validity was carried out through the 17 experts. Descriptive statistical analyses were used to analyze the data. Results: In general the results of the study revealed that half of nurses were at age group (30-39) years , (35%) of study sample was Institute of medical technology/nursing, half of study sample work at obstetric and gynecological ward, (55%) of study sample were married and the highest percentage (93%) their sources of knowledge about Polycystic ovary syndrome from syllabus. Most of the study sample had high assessment level of knowledge about polycystic ovary syndrome. Conclusions: Nurses had high level of knowledge regarding the polycystic ovary syndrome, the reason for this is due to nursing curriculum was effective in giving scientific knowledge about it.